Surface characteristics and cavitation damage progress in ductile materials. (December 2019) - Hutli, Ezddin; Fekete, Tamás; Nedeljkovic, Milos
Abstract: In this paper the investigation and analysis of ductile materials behavior under cavitation bubble collapsing are presented. Three ductile materials (Cu, AlMnMg-alloy, and St.St.316) were treated with cavitation. The cavitating jet generator was used as a tool to produce intensive, fast and severe cavitation phenomenon which is suitable for cavitation damage resistance study. The treated surfaces were characterized in detail by using different microscopy techniques and surface morphology analysis was done. The obtained result shows that the damage process is created by the shearing stress on the surface induced by microjets during cavity collapse. The mechanical properties of the material mainly "fatigue strength" and its Stacking Fault Energy (SFE) played a major role in the damage process. The cavitation damage based on exposure time period starts with surface hardening, followed by plastic deformation and finally by erosion and cracking as a consequence. The in-depth surface characterization using these microscopy techniques provides significant information for monitoring and understanding the cavitation damage mechanism and progress. Energy-dispersive X-ray spectroscopy (EDS) was used to measure the composition of the test materials which helps in the interpretation of the behavior of the material under the cavitation attack. Highlights: Influence of the mechanical properties and microstructures on the cavitation damage mechanisms were investigated. Different microscopy techniques were used for surface characterization. The cavitation damage in the different Ductile materials was analysed. Energy-dispersive X-ray spectroscopy (EDS) was used. A high-speed submerged jet generator was used as tool for cavitation.